5th Annual Progress Reporting and Coordination Meeting on CCAFS Projects and Regional Activities in Southeast Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The proceedings document the results of the 5th Annual Progress Reporting and Coordination Meeting on CCAFS Projects and Regional Activities in Southeast Asia. The report tackles the progress of activities in the CSV sites and on CCAFS project implementation in 2019; the significant outputs and outcomes of FP/CSV implementation; and the knowledge, learning, and experiences across projects.